Review on various voltage stability issues in AC distribution network - Khidrani, Attaullah; Larik, Raja Masood; Memon, Ahsanullah; Bajkani, Irfan Ahmed; Qazi, Sajid Hussain (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
With the rapidly depleting natural energy resources and increasing population worldwide, the calls for more energy demand have risen globally. In this vein, the world is transitioning from traditional to renewable energy sources (RES) to meet the required demands. However, the (RES), due to its variable nature, has voltage stability and power quality issues that need to get minimized to enhance the reliability of the (RES) system. This paper reviews the voltage stability and quality issues in the AC distribution system based on renewable energy sources (RES). Initially the renewable energy sources and problems associated with renewable energy sources are discussed. This article gives an overview of voltage control strategies based on local as well as communication-based phenomenon for distribution networks. In this review a hybrid solar photovoltaic and wind system is used to generate the power of 3-5 kW. A voltage controller topology is suggested using MATLAB/Simulink for enhancing voltage stability of the system. It is suggested that a voltage stability controller can be designed using recommended topology by using Arduino with pulse width modulation technique. Thus, by measuring and correcting real-time voltage instability values of the system, the system can be made more reliably secure, efficient, and stable than the previously proposed renewable AC distribution systems.